Morality in Gaming: Observer Perceptions of Player versus Character Actions - Stansbury, Jessica A; Munro, Geoffrey D; Earnest, David R (Journal of Psychological Perspective, 2024)
The debate on the impact of violent video games and its influence on players continues despite mixed findings. Using the lens of third person perception research, we explored moral judgments of laypersons, those often at the crux of these public debates. Study 1 investigated whether the player or character is perceived by an outside observer as responsible for moral decisions made within the narrative of a violent video game. Study 2 investigated how those perceptions may impact the observers’ perceptions of the player’s future negative behaviors and personality traits. Study 1 and 2 used a 2 (condition: rescuing vs. harvesting) x 2 (role: player vs. character) mixed ANOVA with role as a repeated measure. We created a brief recording of gameplay leading to a moral decision in Bioshock, an interactive, first-person shooter game, shown to participants. Participants were asked to rate perceived morality of player and character actions. Study 1 showed that participants (N = 51) held the observed player more morally responsible for in-game behaviors than the character within the game. Replicating and advancing Study 1, Study 2 (N = 227) showed support for you are what you eat heuristic, in that observers were more likely to view the negative behaviors of the in-game characters as indicators of negative personality traits of the player. These insights are crucial in the broader societal discourse on the potential link between violent video games and real-world aggression